Functional Outcomes of Dual Mobility Cups in Complex Primary Total Hip Arthroplasty: A Prospective Study of 75 Patients - Waseem Ahmad, Tahir Mehmood Khattak, Akhtar Zaman, Kamran Asghar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Total hip arthroplasty (THA) is a common procedure for patients with hip joint disorders; however, dislocation remains a significant complication, especially in complex primary cases. Dual mobility cups (DMCs) have been introduced to enhance stability and reduce dislocation risk. Objective: To evaluate the functional outcomes and complication rates associated with the use of DMCs in complex primary THA. Methods: A prospective study was conducted on 75 patients who underwent complex primary THA using DMCs between January 2022 and October 2023. Functional outcomes were assessed using the Harris Hip Score (HHS) and the Parker Mobility Score (PMS) preoperatively and at 6 and 12 months postoperatively. Complications were recorded during the follow-up period. Logistic regression analysis was performed to identify predictors of functional improvement. Results: The mean preoperative HHS was 42.5 (range 20–60), which improved to 80.2 (range 70–90) at 12 months postoperatively (p<0.001). The mean preoperative PMS was 4.2 (range 2–6), increasing to 7.1 (6–9) at 12 months (p<0.001). No dislocations occurred during the follow-up period. Complications included one case of superficial wound infection and two instances of periprosthetic fractures, all of which were managed conservatively. Conclusion: DMCs in complex primary THA provide excellent functional outcomes with a low complication rate, suggesting their efficacy in enhancing joint stability and patient mobility. Keywords: Dual mobility cup, total hip arthroplasty, functional outcome, dislocation, hip replacement, orthopedic surgery